Encapsulation of ε-Viniferin into Multi-Lamellar Liposomes: Development of a Rapid, Easy and Cost-Efficient Separation Method to Determine the Encapsulation Efficiency - Pauline Beaumont; Arnaud Courtois; Tristan Richard; Stéphanie Krisa; Chrystel Faure (MDPI AG, 2021)
Onion-type multi-lamellar liposomes (MLLs), composed of a mixture of phosphatidylcholine and Tween 80, were analyzed for their ability to encapsulate ε-Viniferin (εVin), a resveratrol dimer. Their encapsulation efficiency (EE) was measured by UV-VIS spectroscopy using three different separation methods-ultracentrifugation, size exclusion chromatography, and a more original and advantageous one, based on adsorption filtration. The adsorption filtration method consists indeed of using syringe filters to retain the molecule of interest, and not the liposomes as usually performed. The process is rapid (less than 10 min), easy to handle, and inexpensive in terms of sample amount (around 2 mg of liposomes) and equipment (one syringe filter is required). Whatever the separation method, a similar EE value was determined, validating the proposed method. A total of 80% ± 4% of εVin was found to be encapsulated leading to a 6.1% payload, roughly twice those reported for resveratrol-loaded liposomes. Finally, the release kinetics of εVin from MLLs was followed for a 77 day period, demonstrating a slow release of the polyphenol.